2008
DOI: 10.4161/cbt.7.6.5837
|View full text |Cite
|
Sign up to set email alerts
|

Static magnetic fields induce blood flow decrease and platelet adherence in tumor microvessels

Abstract: Red blood cell flow in striated muscle capillaries is reduced during exposure to strong static magnetic fields (SMFs). Intratumoral microcirculation is characterized by tortuous microvessels with chaotic architecture and by irregular, sluggish blood flow with unstable rheology.It was the aim of this study to analyze SMF exposure effects on tumor microcirculation with regard to interactions of corpuscular blood components with tumor microvessel walls. In vivo fluorescence microscopy was performed in A-Mel-3 tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 21 publications
1
23
0
Order By: Relevance
“…In that study we observed a reversible reduction of blood flow in tumor vessels as well as activation and adherence of platelets by direct visualization of tumor microcirculation in vivo. 8 proof that tumor microcirculation is affected by SMF exposure. Further, they might explain the previously described phenomenon of improved antitumoral efficacy of conventional chemotherapy if combined with SMF exposure.…”
Section: Introductionmentioning
confidence: 95%
“…In that study we observed a reversible reduction of blood flow in tumor vessels as well as activation and adherence of platelets by direct visualization of tumor microcirculation in vivo. 8 proof that tumor microcirculation is affected by SMF exposure. Further, they might explain the previously described phenomenon of improved antitumoral efficacy of conventional chemotherapy if combined with SMF exposure.…”
Section: Introductionmentioning
confidence: 95%
“…The effects of magnetic field on tumors have been reported in some studies [12]- [15]. After Syrian Golden hamsters bearing A-Mel-3 tumors being exposed to a magnetic field of about 150 mT for short-time, the red blood cell velocity and segmental blood flow in tumor microvessels were significantly reduced [12].…”
Section: Discussionmentioning
confidence: 97%
“…After Syrian Golden hamsters bearing A-Mel-3 tumors being exposed to a magnetic field of about 150 mT for short-time, the red blood cell velocity and segmental blood flow in tumor microvessels were significantly reduced [12]. In vitro, after exposure under 1 T SMF for 72 h, the metabolic activity of human leukemia cell HL-60 was retarded to 81% [13], but exposure to the SMF of 6 mT did not induce any apoptogenic effects in HL-60 cells [14].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, using a dorsal skinfold chamber technique for intravital fluorescence microscopy, Strieth research group demonstrated that SMF exposure ranging 150-600 mT for 3 h induced a significant reduction of functional vessel density, vessel diameters, and red blood cell velocity in tumors (Brix et al 2008;Strieth et al 2008;Strelczyk et al 2009). Exposure to SMF (600 mT for 3 h) resulted in a significant retardation of tumor growth (*30%) (Strelczyk et al 2009).…”
Section: Moderate Intensity Static Magnetic Fields (Smf)mentioning
confidence: 98%